Cardiorespiratory fitness effect may be under-estimated in 'fat but fit' hypothesis studies - Danilo R. Silva; André O. Werneck; Paul J. Collings; David Ohara; Rômulo A. Fernandes; Décio S. Barbosa; Enio R. V. Ronque; Luís B. Sardinha; Edilson S. Cyrino (Taylor & Francis Group, 2017)
Background: Both cardiorespiratory fitness and body fat have been independently related to metabolic syndrome in adolescents; however, the strength of these relationships seems to be dependent on the outcome composition. Aim: To analyse the relationship between cardiorespiratory fitness and body fat combined with different indicators of metabolic risk in adolescents. Subjects and methods: The sample was composed of 957 adolescents (58.7% girls). Cardiorespiratory fitness was obtained using the 20-metre shuttle run test and skinfold thickness was collected for body fat estimation. Metabolic risk score was calculated from waist circumference, systolic and diastolic blood pressure, glucose, HDL cholesterol and triglycerides measurements and an alternative outcome without the central obesity indicator was adopted. Chronological age and somatic maturity were used as covariates. Results: Higher metabolic risk was observed in the highest fat/lowest fit adolescents (p < .05), regardless of sex and outcome. In the regression models, for full metabolic risk score, body fat presented higher coefficients compared to cardiorespiratory fitness in both sexes (boys: 0.501 vs −0.097; girls: 0.485 vs −0.087); however, in the metabolic risk without waist circumference, the coefficients became closer (boys: 0.290 vs −0.146; girls: 0.265 vs −0.120), with a concomitant decrease in body fat and increase in cardiorespiratory fitness coefficients. Conclusion: These findings suggest that body fat is strongly related to cardiovascular risk, but, when the outcome is calculated without the central obesity indicator, cardiorespiratory fitness becomes more related to metabolic risk.